Analisis Pengaruh Kualitas Pelayanan, Kepuasan dan Insentif terhadap Perilaku Word Of Mouth Mahasiswa STIE Pelita Indonesia - Astri Ayu Purwati; Onny Setiawan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
Increasing number of universities in Indonesia today demanding all universities both public and private to be able to improve the quality of competition. One of them is through the right marketing strategy. This study aims to determine the effect of service quality, satisfaction and incentives towardn word of mouth behavior on STIE Pelita Indonesia Pekanbaru students. The sample of this research are 100 respondents who are active students of STIE Pelita Indonesia Pekanbaru and the research method used is multiple linear regression analysis method. The results show that the variable of service quality, satisfaction, incentive partially have significant effect on word of mouth behavior on students. Through this research, the management of STIE Pelita Indonesia need to improve the academic service to the students and to maintain the incentive as one way to promote STIE Pelita Indonesia. Keywords : The quality of service, satisfaction, incentive and word of mouth